Unraveling methylation changes of host macrophages in Mycobacterium tuberculosis infection. (May 2016) - Zheng, Lin; Leung, Eric T.Y.; Wong, H.K.; Lui, Grace; Lee, Nelson; To, Ka-Fai; Choy, K.W.; Chan, Raphael C.Y.; Ip, Margaret
Summary: Objectives: To characterize at high resolution DNA methylation changes of cytokines which occur in the genome of macrophages in association with Mycobacterium tuberculosis (MTB) infection Methods: We studied the methylation profiles of THP-1 derived macrophage cells infected with clinical MTB strains [Beijing/W & non-Beijing/W lineage, sensitive (INH S, RIF S ) & resistant (INH R, RIF R ) strains] and of host macrophages from MTB infected cohorts (active & latent patients) with the human methylation CpG islands microarrays. Results: Methylated modification on the promoter sequences of cytokines and their receptors were found to be associated with MTB infection in a strain- and host-dependent manner. Our epigenetic analyses revealed that infection with Beijing/W MTB strains enhanced IL6R, IL4R and IL17R hyper-methylations in infected macrophages. Validation of IL6R methylated sequence confirmed that MTB infection induced DNA methylation of CpG67 region in the IL6R promoter. In addition, studies on the human macrophage methylation profiles from the patient cohorts indicated that the methylation rate of IL17 family members and related genes were significantly altered in patients with active MTB infections. Conclusions: Our study offered novel insights into the epigenetic changes in the interaction of host macrophages in MTB infections and warrant further explorations into these changes in modulating the immune response in active and latent MTB infections.